2022
DOI: 10.3390/antiox11071250
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Quercetin to Improve the Antioxidant and Regenerative Properties of Frozen or Cryopreserved Human Amniotic Membrane

Abstract: The biological properties of the human amniotic membrane (HAM) and its characteristic ability to be a reservoir of growth factors promoting wound healing make it an ideal biological dressing for the treatment of different clinical conditions, such as burns and non-healing wounds. However, the application of a preservation method on the HAM is required during banking to maintain biological tissue properties and to ensure the release overtime of protein content for its final clinical effectiveness after applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Among these compounds, it has been demonstrated that NAC, thanks to its antioxidant power, is also capable of reducing the damage caused by cryopreservation [ 45 , 46 ]. Another natural compound, quercetin, has been proven not only to counteract the side effects related to cryopreservation but also to enhance the regenerative capacities of the human amniotic membrane, which is currently used in wound healing and burns [ 53 ]. Zang and colleagues have demonstrated that schisandrin B (SchB) supplemented in the storage solution preserved umbilical cord MSCs (UC-MSCs) from injuries associated with cryopreservation.…”
Section: Antioxidants For Perinatal Cellsmentioning
confidence: 99%
“…Among these compounds, it has been demonstrated that NAC, thanks to its antioxidant power, is also capable of reducing the damage caused by cryopreservation [ 45 , 46 ]. Another natural compound, quercetin, has been proven not only to counteract the side effects related to cryopreservation but also to enhance the regenerative capacities of the human amniotic membrane, which is currently used in wound healing and burns [ 53 ]. Zang and colleagues have demonstrated that schisandrin B (SchB) supplemented in the storage solution preserved umbilical cord MSCs (UC-MSCs) from injuries associated with cryopreservation.…”
Section: Antioxidants For Perinatal Cellsmentioning
confidence: 99%